SURVIVAL INDUK BETINA IKAN LELE LOKAL ACEH (Clarias batrachus dan Clarias macrocephalus) YANG DIPELIHARA PADA SUBSTRAT YANG BERBEDA - Muliyana, Agusriati; Hendri, Afrizal; Fadhillah, Radhi (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
Aceh local catfish (variant limbek) is one of the high-potential freshwater fish. It tastes better than sangkuriang catfish so the demand product is higher than supply. Economically, this fish is very potential if developed in aquaculture system, and domesticated. This study aimed to describe the initial stages of domestication of wild fish species through several methods such as (i) broodstocks collection; (ii) broodstocks selection; and (iii) experiment. It was an experimental-single-factor research with three treatments namely; A: no substrate pond; B: soil substrate pond; and C: soil substrate pond with pipe (shelter). The results of the analysis showed that the highest survival rate is in treatment C (a soil substrate pond with pipe) with the first and second sampling percentage of 88% and 68% respectively. The percentage of local catfish that reached the reproductive phase did not differ between the treatment (P>0.05) so the sheltered pond did not affect the reproductive of local catfish, and it was influenced by the quality and quantity of feed.